The Effect of Triangular Fibrocartilage Complex Tear on Wrist Proprioception - Park, Ji Hun; Kim, Dongmin; Park, Heesu; Jung, Inwon; Youn, Inchan; Park, Jong Woong (W B SAUNDERS CO-ELSEVIER INC, 2018)
Purpose This study examined the influence of triangular fibrocartilage complex (TFCC) deep fiber tears on wrist proprioception. Methods The study involved 48 subjects: 24 with deep fiber TFCC tears and 24 with healthy wrists. A specially created sensor measured wrist proprioception in 3 axes of movement. Absolute differences between target and subject-reproduced angles were compared in injured and healthy wrists and in injured and contralateral patient wrists. A greater difference in reproduced angles was deemed to reflect a lesser ability to approximate a target angle. Results In wrists with TFCC injuries, 40 degrees pronation and 60 degrees pronation showed significantly greater differences between target and subject-reproduced angles compared with those in the control wrists. In wrists with TFCC injuries, 40 degrees pronation demonstrated significantly greater differences between target and subject-reproduced angles than did those in patients' contralateral wrists. Proportions of outliers with absolute differences greater than 6 degrees were significantly higher in 60 degrees supination and 40 degrees pronation in wrists with TFCC injuries. Conclusions Deep TFCC fiber detachment may lead to decreased wrist proprioception in 60 degrees and 40 degrees forearm rotation. Copyright (C) 2018 by the American Society for Surgery of the Hand. All rights reserved.